The Right to Labor as a Social and Legal Category - Iskov, Viacheslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article analyzes the concept of «labor», which is characterized as a property of a person, an individual, and ensures the creation of material and spiritual values. The author emphasizes that labor as a human need satisfies not only the interests of an individual, but also of society and the State as a whole. The author establishes that the nature and purpose of labor and its role in the civilization process involve a combination of the need for labor in a creative way, which stimulates human activity in general, and the need for labor as a source of livelihood and resource provision of human capital.It is determined that the right to work as a social category is revealed through its definition as the main way of self-realization of a person who thus expresses his or her inner potential.The author proves that freedom of labor is manifested in the potential possibility for a citizen to choose the sphere of application of his/her labor abilities, and accordingly, the right to labor provides for the possibility of such a choice, and the State facilitates its realization. It is substantiated that the right to work as a legal category indicates that this right is a legally defined and guaranteed opportunity for a person to enter into labor relations, to carry out labor activities with due regard for international labor standards and with the aim of meeting the needs and interests of employees.